Effect of bio-regulators on storage life of plum (Prunus salicina) var. Santa Rosa at different conditions - ATTRI, B L; KRISHNA, HARE; AHMED, NAZEER; KUMAR, AKHILESH (The Indian Journal of Agricultural Sciences, 2015)
The effect of plant bio-regulators, viz. salicylic acid (200ppm), Ca-EDTA (0.4%), thyme oil (100 ppm) and control (distilled water dip) on the postharvest shelf life of plum (Prunus salicina L.) var. Santa Rosa was studied at ambient (18-20oC and 85-90% RH) and low temperature (2oC and 90% RH) conditions for 20 and 55 days respectively. The fruits treated with Ca-EDTA had better retention of firmness followed by salicylic acid and control at ambient and low temperature storage conditions. The highest (22.19%) physiological loss in weight (PLW) was observed in the plum fruits dipped in distilled water as compared to 14.97% in salicylic acid and 15.74% in thyme oil at ambient conditions after 20 days of storage. The maximum and minimum PLW of 3.95 and 2.60% was recorded in the above treatments at low temperature after 55 days of storage. The TSS of the fruits dipped in water and stored at ambient conditions were found to increase for 14 days followed by reduction as compared to other treatments where the TSS increased for 20 days. The maximum reduction in ascorbic acid from 13.64 mg/100g to 8.64 mg/100g was recorded in the water dipped plum fruits stored at ambient conditions for 20 days as compared to the same treatment under low temperature where the reduction was observed from 13.65 to 12.38 after 55 days of storage. The total sugars in the water dipped (control) fruits was found to increase for 6 days followed by decrease at ambient conditions. The fruits treated with salicylic acid showed increase in sugars at the slowest rate compared to Ca-EDTA and thyme oil in both the storage conditions. At both the storage conditions the retention of the antioxidants was better in the SA treated fruits followed by Ca-EDTA and thyme oil.